2014
DOI: 10.1186/1556-276x-9-117
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticle-induced oxidative stress triggers apoptosis by activating JNK signaling pathway in cultured primary astrocytes

Abstract: It has been documented in in vitro studies that zinc oxide nanoparticles (ZnO NPs) are capable of inducing oxidative stress, which plays a crucial role in ZnO NP-mediated apoptosis. However, the underlying molecular mechanism of apoptosis in neurocytes induced by ZnO NP exposure was not fully elucidated. In this study, we investigated the potential mechanisms of apoptosis provoked by ZnO NPs in cultured primary astrocytes by exploring the molecular signaling pathways triggered after ZnO NP exposure. ZnO NP exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 60 publications
7
97
1
1
Order By: Relevance
“…For instance, the ZnO NP-astrocyte interaction was reported to induce an oxidative stress that could trigger cell apoptosis by activating the JNK signaling pathway in cultured primary astrocytes. 107 A similar finding was observed in the interactions between superparamagnetic iron oxide NPs and astrocytes. 108 Mixed glial cultures have often been established from the cerebral cortices of neonatal Sprague-Dawley rats and purified astrocytes.…”
Section: Neurotoxicity On Glial Cells or Neurogliasupporting
confidence: 68%
“…For instance, the ZnO NP-astrocyte interaction was reported to induce an oxidative stress that could trigger cell apoptosis by activating the JNK signaling pathway in cultured primary astrocytes. 107 A similar finding was observed in the interactions between superparamagnetic iron oxide NPs and astrocytes. 108 Mixed glial cultures have often been established from the cerebral cortices of neonatal Sprague-Dawley rats and purified astrocytes.…”
Section: Neurotoxicity On Glial Cells or Neurogliasupporting
confidence: 68%
“…Few studies in literature have documented the biochemical effects of Cu, CuO and ZnO NPs on earthworms in urban soils. The concentrations of NPs found to exhibit adverse effects on earthworms in artificial soils or natural soils tend to be several orders of magnitude lower [32,58,59] than what has been found in this study and other similar studies elsewhere [33,46]. These differences could be due to differences in specific soil characteristics.…”
Section: Hydrogen Peroxidecontrasting
confidence: 60%
“…It has been reported that NPsinduced ROS production and oxidative stress through the MAPK pathway regulates apoptosis. [35][36][37] MAPK plays an essential role in modulating the functions of pro-and antiapoptotic proteins located in mitochondria. For example, JNK has been shown to be critically required for the release of cytochrome c from mitochondria.…”
Section: Discussionmentioning
confidence: 99%